Understanding context and forces for choosing organizational structures for continuous delivery - Ferreira Leite, Leonardo Alexandre; Kon, Fabio; Meirelles, Paulo (Anais Estendidos do Congresso Brasileiro de Software: Teoria e Prática (CBSoft); 2020: Anais Estendidos do XI Congresso Brasileiro de Software: Teoria e Prática, 2020)
In this research, we aim to understand the organizational structures adopted by software-producing organizations for managing IT technical teams in a continuous delivery context. Following Grounded Theory guidelines, we interviewed 46 IT professionals to investigate how organizations pursuing continuous delivery organize their development and operations teams. Among our results, we discovered four organizational structures: (1) siloed departments, (2) classical DevOps, (3) cross-functional teams, and (4) platform teams. After having discovered such structures and their properties, we describe, in this paper, our plans to better understand which contextual properties and forces lead an organization to adopt an organizational structure to the detriment of the other ones.